Noční můry nespí - Březinová, Ivona, 1964-; Tvrdý, Tomáš, 1984-; Šváb, David, 1983-; Mayerová, Klára, 1986-; Holub, Jiří, 1975-; Pomykalová, Zuzana, 1984-; Lyachová, Kristýna, 1986-; Nekuda, René, 1986-; Dziaková, Veronika, 1986-; Kříkava, Tomáš, 1987-; Dlouhá, Anna, 1986-; Heřman, Tomáš, 1983- (E-knihovna, 2016)
Sbírka hororových povídek studentů Literární Akademie Josefa Škvoreckého. Zkrácená verze.